Engaging Italy : American women's utopian visions and transnational networks - Madden, Etta M., 1962- (State University of New York Press, 2022)
"Traces literary and social connections among three American women navigating the changing political landscape of 1860s and '70s Italy"-- Provided by publisher.
Keywords: Women -- Italy -- History -- 19th century.; Americans -- Italy -- History -- 19th century.; Italy -- Politics and government -- 1849-1870.; Femmes -- Italie -- Histoire -- 19e siècle.; Italie -- Politique et gouvernement -- 1849-1870.; LITERARY CRITICISM / Women Authors.; Americans; Politics and government; Women; Italy; 1800-1899; History; Literary criticism.; Critiques littéraires.